THE ANALYSIS OF EARNING MANAGEMENT EFFECT TOWARDS COMPANY'S FINANCIAL PERFORMANCE WITH GOOD CORPORATE GOVERNANCE (GCG) AS THE MODERATOR VARIABLE (RESEARCH ON INFRASTRUCTURE, UTILITY & TRANSPORTATION SECTOR COMPANY LISTED ON IDX IN 2014-2017) - MARIA EKRISTA OKTAVIANA DEWI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research is aimed to obtain investigate the effect of earning management towards financial performance with good corporate governance as the moderator variable. This research use 24 data frominfrastructure, utility & transportation sector companies listed on Indonesia Stock Exchange in the period of 2014-2017. This research which use Moderated Regression Analysis (MRA) as research analysis method shows that the earning management provide significant effect towards company's financial performance. Institutional ownership and independent board of commissioners is able to moderate the effect of earning management towards financial performance, so that institutionalownership and independent board of commissioners is the moderator variable. However, managerial ownership is not moderator variable. Keywords: financial performance, profit management, institutional ownership, managerial ownership, and independent board of commissioners.